(untitled) (Journal of Student Affairs in Africa, 2024)
A critical area of debate in an era of evolving university support systems is student support in challenging disciplines. This study examines the effectiveness of current frameworks in addressing the needs of engineering students. This research employs a mixed-methods approach to identify the experiences of final-year Bachelor of Engineering Technology students, lecturers and support staff at Nelson Mandela University. The study finds a direct relationship between students’ stress levels and their resilience, highlighting the importance of well-structured support systems, including orientation programmes and subject-specific tutoring. This article introduces a novel perspective on fostering academic resilience in engineering education, advocating a comprehensive approach that integrates personal, academic, and socio-ecological aspects of support. Challenging conventional views of interventions for student success, it proposes a new, holistic framework for higher education institutions. This approach could contribute to enhancing student resilience and success and provides a fresh lens to address student dropout in South African higher education and beyond.